FAKTOR-FAKTOR KEBERHASILAN PENGOBATAN PASIEN TUBERKULOSIS RESISTEN RIFAMPISIN (TB-RR) DI PROVINSI JAMBI - Helmi Suryani Nasution; Ria Rizky; Ashar Nuzulul Putra; Marta Butar Butar (Jurnal Penelitian Kesmasy, 2026)
The success rate of drug-resistant tuberculosis (DR-TB) treatment in Jambi Province has not yet reached the target. This study aims to determine factors contributing to treatment success in patients with rifampicin-resistant tuberculosis (RR-TB) in Jambi Province. The study was conducted in Jambi Province using a retrospective cohort design. Data were obtained from the Tuberculosis Information System (SITB) for the period 2020–2023. A total of 122 patients were included using a total sampling technique. The inclusion criteria comprised patients who received treatment between 2020 and 2023 with complete data. Exclusion criteria included patients who had not completed treatment, had incomplete or duplicate data, or whose treatment outcomes had not been evaluated. The instrument used was the TB RO.03 report. Data were analyzed using the Chi-square test and log-linear Poisson regression. The treatment success rate for RR-TB was 61.5%. Age was significantly associated with treatment success, with an adjusted relative risk (aRR) of 1.65 (95% CI: 1.03–2.66). In contrast, no significant associations were found between treatment success and gender, history of previous treatment, anti-tuberculosis drug regimen, diabetes mellitus status, or HIV status. Age was identified as the most dominant factor influencing treatment success. Therefore, special attention should be given to patients aged over 50 years to improve TB treatment outcomes.